Respons Emotional Well-Being Dalam Laras Gamelan Jawa - Djohan (Mudra Jurnal Seni Budaya, 2008)
The aim of these research is to study the effects of laras toward the listener emotional well-being. From the psychology of music point of view, this research attempts to understand the emo- tional well-being of the listeners. These study may be primarily cog- nitive or may consist of the frequency with which listener expe- rienced pleasant and unpleasant emotions. The samples were every- one whose have an experienced on listening the gamelan in their everyday life. Through quasi-experiment and purposive sampling, the 73 samples listened to two songs that composed in slendro nem and pelog lima’s scale and also interviewed in focus group discus- sions. The results shown that the pelog’s scale influenced more to the emotional well-being of the listeners than slendro’s scale.